An Exploration of Cyclists' Preferences that Influence Route Choice to Recreation in Yogyakarta during COVID-19 - Isheka, Raihan Pasha; Habibi Kamal, Muhammad Iqbal; Suryadwanti, Novia; Radiansyah, Kusuma Aji (Universitas Negeri Yogyakarta, 2023)
People's travel behavior has changed significantly as a result of the COVID-19 pandemic. The growing number of cyclists, particularly those who ride for recreation, and how they view the options for recreational riding routes are two of the elements that are being impacted. Cycling route preferences may be viewed differently than they were prior to the pandemic. It will be crucial to understand cyclists' behavior while choosing their routes in order to choose the development, especially for cycling infrastructure. This research aims to explain the perceptions of recreational cyclists regarding the influential factors in determining their routes. The data for this study was collected from 340 respondents who use bicycles for recreation in Yogyakarta City. A questionnaire was used to collect data by examining the factors that influence cyclists in determining their routes, such as infrastructure conditions, traffic conditions, environmental conditions, and travel plans, using a Likert scale. Through the questionnaire, socio-demographic characteristics of the respondents were obtained, revealing that the majority were male, with incomes below Rp 1,500,000, and aged below 25 years. The analysis methods used in this study were descriptive analysis, importance score analysis, and chi-square tests between the characteristics of the cyclists and each factor. The results showed that the most important factors for recreational cyclists in determining their routes in Yogyakarta City are the availability of street lighting facilities (4.34), good road conditions (4.31), the presence of dedicated bicycle lanes (4.30), low traffic volume (4.30), and the natural environment (4.29). Additionally, the frequency of recreational cycling statistically correlates significantly with some factors, such as the availability of bicycle lanes, bike boxes, and low pollution levels.